Peran Kualitas Komunikasi dan Keintiman terhadap Komitmen Pernikahan pada Pasangan Dual career di Organisasi Perangkat Daerah Kabupaten Serang - Vania Shavina Santri; Jane Savitri; Jacqueline Tjandraningtyas (Humanitas (Jurnal Psikologi), 2022)
The purpose of this study was to determine the role of communication quality and intimacy both jointly and partially on marital commitment in dual career couples in Serang Regency Regional Apparatus Organizations. This study uses Rusbult and Buunk's theory of marital commitment, 1993; in Arriaga & Agnew 2001), quality of communication in Montgomery (1981), and Schaefer and Olson (1981; in Weeks and Hof, 1995). This study used a quantitative method with 380 dual career husband/wife subjects in the Serang Regency Regional Apparatus Organization. The research data was processed using multiple regression and linear regression. Based on the analysis conducted in this study, it is known that: the quality of communication and intimacy together have a role in marital commitment (F = 35.508 ; R2 = 0.353 ; ρ < .05). Partial calculations show that the quality of communication and emotional intimacy have a role in marital commitment, while other variables do not have a role in marital commitment.